A Patient Presenting with Concurrent Testis Torsion and Epididymal Leiomyoma - E. Arpali; A. Tok (Case Reports in Urology)
Leiomyomas are the second most common tumors of epididymis. Patients with leiomyomas are sometimes misdiagnosed with testicular tumors. A Case of a patient with a scrotal mass presenting with testicular torsion is reported. Concurrent occurrence of testicular torsion and epididymal leiomyoma is an extremely rare condition.